Transcriptomal signatures of vaccine adjuvants and accessory immunostimulation of sentinel cells by toll-like receptor 2/6 agonists. Issue 7 (3rd July 2018) - Salyer, Alex C. D.; David, Sunil A.
ABSTRACT: An important component of vaccine development is the identification of safe and effective adjuvants. We sought to identify transcriptomal signatures of innate immune stimulating molecules using next-generation RNA sequencing with the goal of being able to utilize such signatures in identifying novel immunostimulatory compounds with adjuvant activity. The CC family of chemokines, particularly CC chemokines 1, 2, 3, 4, 7, 8, 17, 18, 20, and 23, were broadly upregulated by most Toll-like receptor (TLR) and nucleotide-binding domain and leucine-rich repeat–containing receptors (NLR) stimuli. Extracellular receptors such as TLR2, TLR4 and TLR5 induced the transcription of CXC chemokines including CXCL5, CXCL6 and CXCL8, whereas intracellular receptors such as TLR7 and TLR8 upregulated CXC chemokines 11 and 12. Both TLR1/2 and TLR2/6 agonists induced strong chemokine production in human peripheral blood mononuclear cells. Human skeletal muscle cells and fibroblasts respond with chemokine production only to TLR2/6 agonists, but not TLR1/2 agonists, consistent with strong expression of TLR2 and TLR6, but not of TLR1, in fibroblasts. TLR2/6 stimulated fibroblasts demonstrated functional chemotactic responses to human T cell and natural killer cells subsets. The activation of non-hematopoietic, adventitial cells such as fibroblasts and myocytes may contribute.